Mempertimbangkan Spiritualitas Ekonomi Berdasarkan Intuisi Kosmotheandrik Raimundo Panikkar - Yan Okhtavianus Kalampung (Faculty of Theology Duta Wacana Christian University, 2016)
Abstract This essay going to argue that Raimundo Panikkar's concept of Cosmotheandric Intuition has strong significance in forming an economics spirituality. Economics system nowadays tend to become a system of greediness. By considering cosmology concept such as cosmotheandric intuition and its significant relation, writer made a counter spirituality to all of negative effect of capitalism economics. At the first part of this paper will briefly explain about Raimundo Panikkar and his proposal of Cosmotheandric Intuition. After showing problems in contemporary economics discourse, this paper explain the meaning of spirituality, as a basis understanding to form an economics spirituality. At the part of analysis about economics spirituality, writer wrote counter arguments to capitalist economics system based on Cosmotheandric Intuition. Therefore writer find it usefull to form an economics spirituality based on it. Abstrak Tesis tulisan ini adalah konsep Intuisi Cosmotheandris dari Raimundo Panikkar bisa menjadi bahan yang baik untuk membentuk sebuah spiritualitas ekonomi. Sistem ekonomi masa kini semakin menjadi sistem keserakahan. Dengan mempertimbangkan konsep kosmologis seperti Intuisi Kosmotheandris dan relasinya yang mendalam, penulis membuat sebuah pertimbangan spiritualitas sebagai argumen balik untuk efek-efek negatif dari ekonomi kapitalis. Pada bagian pertama dari makalah ini, penulis akan secara singkat menjelaskan tentang sosok Raimundo Panikkar dan usulannya tentang Intuisi Kosmotheandris. Setelah memperlihatkan masalah-masalah kontemporer dari diskursus ekonomi, makalah kemudian menjelaskan makna dari spiritualitas sebagai pengertian dasar untuk merumuskan sebuah spiritualitas ekonomi. Pada bagian analisis tentang spiritualitas ekonomi, penulis mencantumkan argumen balik terhadap sistem ekonomi kapitalis berdasarkan Intuisi Kosmotheandrik dengan menjelaskan beberapa tema khusus yang mempunyai kaitan dengan hal tersebut. Berdasarkan hal itu, penulis menemukan bahwa konsep Intuisi Kosmotheandris berguna untuk membentuk sebuah spiritualitas ekonomi.